Pengaruh Kualitas Pelayanan dan Persepsi Harga terhadap Kepuasan Konsumen pada Usaha Omah Petoeng Tulungagung - Sabilla Rizqiana; Muhammad Alhada Fuadilah Habib (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
Omah Petoeng is a business place that operates in the culinary business with the angkringan concept which is currently developing in Tulungagung City. The quality of service provided by Omah Petoeng employees is good, friendly and fast. Apart from that, the prices of food and drinks are quite affordable for the community, making Omah Petoeng visited by many consumers, including young people, adults and the elderly, therefore Omah Petoeng's sales turnover has experienced a good increase every year. The aim of this research is to determine the influence of service quality and price perception on consumer satisfaction at the Omah Petoeng Tulungagung business. This research uses a quantitative approach with the type of research, namely associative, namely a type of research that explains the relationship between variables. The population in this research is consumers who have visited and made purchases at Omah Petoeng Tulungagung. The data collection technique uses a questionnaire addressed to respondents to answer. The results of the data were then analyzed using tests in SPSS 16. The research results showed that: (1) service quality and price perception had a significant effect on consumer satisfaction at the Omah Petoeng Tulungagung business, (2) service quality had a positive and significant effect on consumer satisfaction in the Omah Petoeng Tulungagung business, (3) price perception has a positive and significant effect on consumer satisfaction in the Omah Petoeng Tulungagung business.